Analisis Faktor Yang Mempengaruhi Effective Tax Rate - Vidiyanna Rizal Putri (Jurnal Akuntansi Keuangan dan Bisnis, 2018)
The purpose of this research is to examine and analyze the relation of profitability, leverage, capital intensity and Institusional ownership against tax avoidance proxied by ETR. The sample selection using purposive sampling method and observation from this research is as many as 7 construction companies listed in BEI. Data obtained from secondary data of financial statements of construction companies, starting from 2012 until 2016. Analysis technique used in this research is multiple linear regression analysis. The hypothesis in this study is based on previous research and various other supporting theories. The results of this study indicate that Capital intesity and institusional Ownership have no effect on tax avoidance and profitability and leverage  have a significant positive effect on tax avoidancein construction companies.Keywords : Profitability, Leverage, capital intensity, institusional ownership, Tax Avoidance